Evaluantion of the potential of Trichoderma harzianum and Bacillus subtilis in the solubilization of phosphorus in corn culture - Gonilha, Dalilla Berlanda de Lima [UNESP] (2025)
Corn has significant importance in the Brazilian economy because of its versatility and multiple purposes of use. To ensure or increase the productivity of maize crops, it is essential to continuously supply the necessary nutrients, particularly through the application of nitrogen and phosphate fertilizers. Although soils contain a good amount of phosphorus, this nutrient is adsorbed in the clay fraction and is unavailable to plants, necessitating the use of a large amount of phosphate fertilization. Some microorganisms, including the fungi Trichoderma harzianum and Bacillus subtilis, can synthesize organic acids and enzymes such as phytase and phosphatase that solubilize inorganic and unavailable phosphorus, making it available to plants and microorganisms. To solve this problem, a sustainable alternative is the use of biofertilizers. Therefore, the objective of this study was to evaluate the efficacy and adequate dosage of fertilization combined with inoculation of the fungus Trichoderma harzianum and the bacterium Bacillus subtilis under greenhouse conditions. The study included 10 treatments with 5 replicates each. The control treatment consisted of 100% fertilization. The other treatments combined different levels of fertilization (0%, 50% and 100%) with the microorganisms Trichoderma harzianum and Bacillus subtilis, either alone or in combination. Height, stem diameter, shoot and root dry matter, root volume, phosphorus concentration and chlorophyll content were evaluated. The treatments with no fertilization presented the lowest values for almost all the parameters. The inoculation alone, without mineral fertilization, was not able to maintain parameter values as those found in the control that received mineral fertilization. However, those that received inoculation or a reduced dosage presented similar parameters to those of the control. These results suggest that it is possible to reduce nitrogen and phosphate fertilization in maize via microorganisms without causing damage to the crop.